Analysis of Pragmatic Discourse in the Concept of Language Conversation - Ratna sari; Filda fitriani (Demagogi: Journal of Social Sciences, Economics and Education, 2024)
One approach used to describe language is discourse analysis. This term was first used by Zellig Harris in 1952 as the name for a method of analyzing speech (or writing) that has relationships. This method was originally intended to look for correlations between language and culture (Malmkkjaer, 1995: 100). This pragmatic discourse analysis examines a continuous series of theoretical concepts and practices in both spoken and written discourse which is broader than sentences in various contexts. This study is very interesting in interdisciplinary linguistics, this study can be applied differently according to the point of view and discourse context. including textual and contextual discourse analysis in pragmatic discourse. This discourse can take the form of utterances which are speech events that can be recognized (without reference to the linguistic structure), such as conversations, jokes, sermons, interviews, both in print and electronic media that are close to everyday life.